Barriers to ICT Integration in Elementary Physical Education: Evidence from Tual City, Maluku Province - Rudolf Kempa; Arnold Sahalessy; Mieke Souisa; Vicktor Henry Rony Apituley (CV FOUNDAE, 2025)
The difference in the use of Information and Communication Technology (ICT) between the 3T (frontier, outermost, and disadvantaged) regions poses an enormous challenge towards achieving equitable quality education, particularly in practice-based Physical Education (PJ) subjects. Remote island districts such as Tual City, Maluku Province, face severe issues regarding infrastructure, internet access, and teacher professional development. The aim of this study is to study the integration of ICT and identify the challenges faced by elementary school distance learning teachers in Tual City. Descriptive qualitative research was conducted, data collected through class observations, semi-structured interviews, and documentation of 13 distance learning teachers. The results revealed that 69.2% of the participants had a good idea of ICT, while 30.8% of them had limited knowledge. Although all the participants agreed that ICT can be utilized in learning, a significant disparity was found between classroom practice and self-reported use. Instructional videos, laptops, and PowerPoint were quoted most often, but actual implementation is still in its infancy. Significant obstacles are internal in nature such as low digital literacy and teacher motivation and external such as poor policy support, limited school infrastructure, and poor internet connectivity. The study recommends context-specific ICT education, constructing digital infrastructure, and adaptive policy to support teachers in remote areas. The study contributes theoretically by identifying the application of ICT in less researched practice-based fields, and contributes to policy for the promotion of technology implementation in 3T (third-to-third) territories